Asynchronization in JavaScript and asynchronous state in the application - Sapalskyi, Oleksandr (National Technical University "Kharkiv Polytechnic Institute", 2024)
JavaScript, as a single-threaded programming language, uses asynchronous programming to perform multiple operations simultaneously. Asynchronous code allows you to run operations without waiting for them to complete, thus improving performance and responsiveness of the interface. This paper discusses the problems of managing asynchronous state in JavaScript applications, as well as the methods and tools used to solve them.
Keywords: asynchronous programming; JavaScript; state control; programming languages